2020
DOI: 10.1021/acs.langmuir.0c01463
|View full text |Cite
|
Sign up to set email alerts
|

Peering into the Formation of Cerium Oxide Colloidal Particles in Solution by In Situ Small-Angle X-ray Scattering

Abstract: The formation of CeO2 colloidal particles upon heating an aqueous solution of (NH4)2Ce­(NO3)6 to 100 °C was investigated by time-resolved in situ SAXS analysis using synchrotron radiation, providing absolute intensity data. In particular, the experiments were performed by applying different temperatures between room temperature and 100 °C as well as under variation of the ionic strength and concentration. Using validated SAXS evaluation tools (SASfit and McSAS software), the analyses revealed the presence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 37 publications
4
23
2
Order By: Relevance
“…Therefore, it is suggested that the initial hydrolysis of cerium cations leads to formation of these crystallites near-independent of the physicochemical environment. Small-angle X-ray spectroscopic studies have shown that Ce 4+ species undergo immediate hydrolysis under aqueous conditions to form polycation species of unique repeat numbers. , Further, the lengths of these phases have been related to the physicochemical environment, suggesting that aggregation of primary crystallites will be related to the degree of hydrolysis undergone by the species and function as a primary determinant for the polycrystalline particle product. In one such study, the dissolution of cerium nitrate salt led to the immediate formation of clusters ∼1.6 nm in size .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is suggested that the initial hydrolysis of cerium cations leads to formation of these crystallites near-independent of the physicochemical environment. Small-angle X-ray spectroscopic studies have shown that Ce 4+ species undergo immediate hydrolysis under aqueous conditions to form polycation species of unique repeat numbers. , Further, the lengths of these phases have been related to the physicochemical environment, suggesting that aggregation of primary crystallites will be related to the degree of hydrolysis undergone by the species and function as a primary determinant for the polycrystalline particle product. In one such study, the dissolution of cerium nitrate salt led to the immediate formation of clusters ∼1.6 nm in size .…”
Section: Resultsmentioning
confidence: 99%
“…Small-angle X-ray spectroscopic studies have shown that Ce 4+ species undergo immediate hydrolysis under aqueous conditions to form polycation species of unique repeat numbers. , Further, the lengths of these phases have been related to the physicochemical environment, suggesting that aggregation of primary crystallites will be related to the degree of hydrolysis undergone by the species and function as a primary determinant for the polycrystalline particle product. In one such study, the dissolution of cerium nitrate salt led to the immediate formation of clusters ∼1.6 nm in size . It was determined that aging in the chemical environment then leads to primary particle formation with the growth mechanism dependent on the solution pH, the cerium concentration, and the solution ionic strength.…”
Section: Resultsmentioning
confidence: 99%
“…For the hydroxo-bridging ligands such as -OH and η-OH, SAXS revealed a hierarchical structure with an aggregated shape of rigid globules, because the primary and secondary clusters grew at different rates. To the best of or knowledge, such results have not been reported in the literature except for Smarsly et al, 49 possibly due to a lack of advanced techniques or interest. Ions, complexes, dimers, trimers, 38-and 40-mers, etc.…”
Section: Methodsmentioning
confidence: 89%
“…Remarkably, Smarsly et al recently reported CeO2 colloidal particles similar to ours and proposed the synthetic pathways for particle formation. 49 However, their advanced work only characterised the agglomerates as products via their original protocols and did not perform in-situ observation of the secondary clusters. In this respect, the present study is not a simple extension of prior work, since it mainly focuses on the hierarchical structure itself via in-situ observation using high-resolution TEM and Raman spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wang et al synthesized silica doped CeO 2 nanostructure as NH 3 gas sensors, which achieved a 0.5 ppm detection limit and 3244% response to 80 ppm NH 3 [16]. But usually, CeO 2 nanomaterials are easy to agglomerate, which makes the gas sensing performance of CeO 2 nanomaterials decrease rapidly [17]. Compared with nanoparticles, 1D nanofibers have a large aspect ratio, which means that more surface atoms are involved in the surface gas-solid reaction.…”
Section: Introductionmentioning
confidence: 99%